2018
DOI: 10.1007/s12649-018-0334-6
|View full text |Cite
|
Sign up to set email alerts
|

Composts and Water Extracts of Lignocellulosic Composts in the Aspect of Fertilization, Humus-Forming, Sanitary, Phytosanitary and Phytotoxicity Value Assessment

Abstract: Purpose Lignocellulosic biomass waste is produced in large quantities and only a small part is used for utility purposes. The aim of the work was to assess the fertilization value of the solid fraction and water extract of lignocellulosic composts. Methods Compost I contained 42.86% pine bark, 34.28% grass, 20.0% sawdust and 2.86% chicken feathers; compost II contained 25.54% pine bark, 10.63% wheat straw, 51.07% sawdust and 12.76% chicken feathers. Seldom described physical properties and phytosanitary and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…To evaluate the compost maturity and their phytotoxicity, a germination assay was conducted with corn seeds and the Germination Index (GI) was determined according to [5]- [17]. The germination test was carried out (in triplicate) on filter paper in petri dishes.…”
Section: Phytotoxicity Testmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the compost maturity and their phytotoxicity, a germination assay was conducted with corn seeds and the Germination Index (GI) was determined according to [5]- [17]. The germination test was carried out (in triplicate) on filter paper in petri dishes.…”
Section: Phytotoxicity Testmentioning
confidence: 99%
“…A maturation phase starts from the 49th day (temperature equal to 25 °C). During this phase, the temperatures of the treatments were confused with the ambient temperature [5] which showed that there was no longer any significant activity of the microorganisms. During this phase, precursors of humus and slow degradation of resistant compounds slowly appear [3], resulting in a dark brown to black coloration of the compost and making it thinner and more homogeneous [25]- [26].…”
Section: Composting Processmentioning
confidence: 99%
See 3 more Smart Citations